2022
DOI: 10.55927/fjas.v1i6.1808
|View full text |Cite
|
Sign up to set email alerts
|

Factors Inhibiting the Implementation of the Package B Program at SPNF SKB Bolangitang, Bolaang Mongondow Utara Regency

Abstract: This study aims to determine the inhibiting factors for the implementation of B Package  in SPNF SKB Bolangitang, North Bolaang Mongondow Regency. In this study, the focus of the problem is socialization, infrastructure, human resources, and budget. The results of this study in terms of several problems that hinder as follows: the socialization that has been carried out has been running but is not optimal due to lack of budget and resources. However, socialization is still carried out with other alternatives, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Insufficient facilities and infrastructure found that the facilities and infrastructure at the Love Tree Beach tourist attraction need to be rehabilitated the rehabilitation process is still at the application stage, and obstacles in the rehabilitation of facilities and infrastructure are caused by insufficient funding [16]. As a result of insufficient funding, the rehabilitation phase of facilities and infrastructure has been hampered and the development of the Love Tree Beach tourist attraction has also been hampered.…”
Section: Factors Inhibiting the Implementation Of Tourism Development...mentioning
confidence: 99%
“…Insufficient facilities and infrastructure found that the facilities and infrastructure at the Love Tree Beach tourist attraction need to be rehabilitated the rehabilitation process is still at the application stage, and obstacles in the rehabilitation of facilities and infrastructure are caused by insufficient funding [16]. As a result of insufficient funding, the rehabilitation phase of facilities and infrastructure has been hampered and the development of the Love Tree Beach tourist attraction has also been hampered.…”
Section: Factors Inhibiting the Implementation Of Tourism Development...mentioning
confidence: 99%
“…Inability to utilize information technology optimally to support rapid reaction team operations, even though the use of information and digital technology is very important to support coordination, monitoring, and reporting during disaster management. However, the lack of budget for the procurement of software, communications networks, and hardware results in limited use of information technology [10]. Apart from that, personnel skills and training in the use of information technology are also still low.…”
Section: Introductionmentioning
confidence: 99%